EDUCATIONAL NEEDS OF ADOLESCENT MOTHERS ON THE STAGE POSTPARTUM - Molina Chávez, Rebeca (2010)
The following article presents the results of the diagnostic phase of the Educational Program of Nursing for the Postpartum Stage directed to Adolescent Mothers in the Health Area of San Juan, San Diego and Concepción and the “Fundación Reciclando Esperanzas”. The diagnostic phase was attended by 13 teenage mothers during the month of July, 2007. The information was collected through the application of a questionnaire, called a "pretest", which allowed the characterization of the population as well as identifying the educational needs of the postpartum stage. The analysis was conducted by grouping the data according to the categories raised in the questionnaire. The educational needs encountered in the diagnosis related to the following topics: physical and psychological changes in the postpartum stage, lifestyle in the postpartum stage, family planning, breast feeding, and care and stimulation of the newborn.